An unusual dyspnea in an 87-year old woman affected by Sjögren's syndrome - Carlo Grendene; Anna Francesca Guerra; Stefania Cerri; Antonello Pietrangelo; Massimo Fiorini (Verduci Editore, 2021)
Primary Sjögren's syndrome (pSS) is a progressive autoimmune disease and is characterized by eye and mouth dryness due to lymphocytic infiltration in lacrimal and salivary glands leading to tissue destruction, but it can also present systemic manifestations including lung involvement. Respiratory manifestations in pSS have a prevalence of 9-20% and can be due to airway and/or lung parenchyma involvement, such as in particular in interstitial lung diseases like lymphocytic interstitial pneumonia (LIP). LIP is an inflammatory diffuse parenchymal lung disease, which is almost invariably associated with other conditions, such as autoimmune diseases and immunodeficiency states, and usually affects women with a mean age of 50 years. We described a case of patient with LIP who was referred to our Internal Medicine Unit and the diagnostic issues related to the patient age and comorbidities.